Perbandingan efektivitas penggunaan pasta gigi herbal dan non herbal terhadap penurunan indeks plak - Luh Gede Pradnya Jati Wulandari; Sari Kusumadewi; Putu Lestari Sudirman (School of Dentistry Faculty of Medicine Udayana University, 2020)
Background: Dental plaque is a microbial biofilm, it contains a various microorganism that produce many enzymes, toxins, and lipopolysaccharides. The effective way to remove dental plaque is tooth brushing with dentifrice. Nowadays, there were various herbal and non-herbal dentifrices with the advantages and disadvantages of each dentifrice.Objective: To compare the effectiveness of herbal and non-herbal dentifrices in reducing dental plaque index.Methods: This study used true experimental with pre-test and post-test control group design. Thirty four participants were randomly allocated to two groups, the herbal group and the non-herbal group. The subjects were asked to brush twice daily with Ciptadent dentifrices, for 7 days, using Bass technique. Dental plaque index were recorded according to O’Leary Index method. Result: The mean score of dental plaque index at the post-test was found 12.05 ± 6.76 for the herbal group and 26.75 ± 13.20 for the non-herbal group. The independent sample t-test showed a difference in the mean score of dental plaque index in both group was found 14.70 (CI 95%: 7.37-22.03; p=0.007).Conclusion: The herbal dentifrice was more effective in reducing dental plaque index. Latar belakang: Plak merupakan suatu microbial biofilm, terdiri dari berbagai jenis mikroorganisme yang memproduksi sejumlah enzim, toksin, dan lipopolisakarida. Cara efektif untuk menghilangkan plak adalah dengan menggosok gigi menggunakan pasta gigi. Saat ini terdapat berbagai jenis pasta gigi herbal dan non herbal dengan kelebihan dan kekurangannya masing-masing.Tujuan: Mengetahui perbandingan efektivitas penggunaan pasta gigi herbal dan non herbal terhadap penurunan indeks plak.Metode: Penelitian ini bersifat true experimental dengan rancangan pre-test and post-test control group design. Tiga puluh empat sampel dibagi menjadi dua kelompok, yaitu kelompok pasta gigi herbal dan non herbal. Sampel diminta untuk menyikat gigi menggunakan pasta gigi Ciptadent yang diberikan sebanyak 2 kali selama 7 hari, menggunakan teknik Bass. Pengukuran indeks plak pre-test dan post-test menggunakan metode O’Leary Index.Hasil: Rerata indeks plak post-test pada kelompok herbal adalah 12,05 ± 6,76 dan pada kelompok non herbal adalah 26,75 ± 13,20. Analisis independent sample t-test menunjukkan beda rerata indeks plak pada kedua kelompok adalah 14,70 (IK 95%: 7,37-22,03; p=0,007).Simpulan: Penggunaan pasta gigi herbal lebih efektif dalam menurunkan indeks plak.